2011
DOI: 10.1039/c0cc05278g
|View full text |Cite
|
Sign up to set email alerts
|

Heating and separation using nanomagnet-functionalized metal–organic frameworks

Abstract: A magnetic functionalization of microcrystalline MOF particles was realized using magnetic iron oxide particles. Such magnetic MOFs can be separated using a static magnetic field after use in catalytic processes and heated by an external alternating magnetic field to trigger desorption of encaged drug molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
129
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 30 publications
2
129
0
Order By: Relevance
“…For example, Fe(OH)(bdc) exists as two polymorphs, a monoclinic phase (Fe-MIL-53) and a hexagonal 95 phase (Fe-MIL-88B) which differ in how the octahedral FeO 6 building units are arranged. Preparation of a mother solution of these components yields two products: monoclinic Fe-MIL-53 as a result of homogeneous nucleation during solution aging, and Fe-MIL-88B deposited on a carboxylate-terminated SAM An alternative gel-layer strategy has recently been reported by Schoedel et al, which allows higher concentrations of reactants to 10 be employed and removes the need to precondition reaction solutions.…”
Section: Mofs At Metal/sam Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fe(OH)(bdc) exists as two polymorphs, a monoclinic phase (Fe-MIL-53) and a hexagonal 95 phase (Fe-MIL-88B) which differ in how the octahedral FeO 6 building units are arranged. Preparation of a mother solution of these components yields two products: monoclinic Fe-MIL-53 as a result of homogeneous nucleation during solution aging, and Fe-MIL-88B deposited on a carboxylate-terminated SAM An alternative gel-layer strategy has recently been reported by Schoedel et al, which allows higher concentrations of reactants to 10 be employed and removes the need to precondition reaction solutions.…”
Section: Mofs At Metal/sam Interfacesmentioning
confidence: 99%
“…15) The membrane was also successfully tested in liquid separation: pervaporation studies of 90 ethyl acetate azeotropes demonstrated the water concentration of the permeate could be enhanced from 7 to 99%. This is one of the few examples of liquid separation using MOF-oxide composite membranes, and the selectivity likely arises from the favourable entry of water into the MIL-53 pores which are lined by the 95 terminal hydroxyl groups of the framework SBU. HKUST-1 membranes have also been prepared from a preoxidised copper net as the porous support.…”
mentioning
confidence: 99%
“…This strategy has been widely used in developing zeolite-based photocatalysts 20 and recently in preparing MOF/nanocomposite or MOF/molecular catalyst hybrids, 19,21,22 yet suffers from challenges, notably the difficulty in preventing the guest material aggregation and the lack of the control over spatial distribution and homogeneity. 21,[23][24][25][26] An alternative approach, which has recently been used in developing photoactive MOFs, is to develop the framework which exhibits an intrinsic photochemical response and thereby can be directly applied in photocatalysis. 27,28 As photocatalysis is based on a charge-transfer (CT) event following photoexcitation, it is essential to gain an intimate knowledge of the excited-state and charge transport properties within the ZIF framework, the properties that remain unexplored.…”
mentioning
confidence: 99%
“…Several materials such as polyoxometalate (POM), 21,[23][24][25][26] iron oxide [27][28][29] and graphite oxide (GO) [16][17][18][19][20] have been used for the formation of MOF composites. POM/MOF composites have been used in various fields including acid catalyses, oxidation catalyses, adsorption/decontamination and so on.…”
Section: -12mentioning
confidence: 99%